2004
DOI: 10.1007/s00267-004-0261-0
|View full text |Cite
|
Sign up to set email alerts
|

Using Wildlife as Receptor Species: A Landscape Approach to Ecological Risk Assessment

Abstract: To assist risk assessors at the Department of Energy's Savannah River Site (SRS), a Geographic Information System (GIS) application was developed to provide relevant information about specific receptor species of resident wildlife that can be used for ecological risk assessment. Information was obtained from an extensive literature review of publications and reports on vertebrate- and contaminant-related research since 1954 and linked to a GIS. Although this GIS is a useful tool for risk assessors because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…For example, male 501 with the largest home range also had the highest transfer factor from sediment to crab for both Hg and PCBs possibly since the bird potentially foraged (and samples were collected) over a larger area, thus not providing an accurate picture of the true contaminant ratio between sediment and crabs. These findings reinforce the notion the area of contamination to home range ratio is extremely important to understand contaminant mobility (Gaines et al 2004). However, even the sediment sampled in the smallest home ranges (e.g.…”
Section: Home Rangesupporting
confidence: 72%
“…For example, male 501 with the largest home range also had the highest transfer factor from sediment to crab for both Hg and PCBs possibly since the bird potentially foraged (and samples were collected) over a larger area, thus not providing an accurate picture of the true contaminant ratio between sediment and crabs. These findings reinforce the notion the area of contamination to home range ratio is extremely important to understand contaminant mobility (Gaines et al 2004). However, even the sediment sampled in the smallest home ranges (e.g.…”
Section: Home Rangesupporting
confidence: 72%
“…These sites were about four-fold larger than the average home range size of common small mammals in our study area. For example, in a study in southern Texas, Merriam's pocket mouse (Perognathus merriami Allen) moved a maximum distance of 46 m; the home range of hispid cotton rats (Sigmidon hispidus Say and Ord) was 1 ha for males and 0.5 ha for females (Chapman and Packard 1974;Gaines et al 2004). Stickel and Stickel (1949) reported that the home range of the northern pygmy mouse (Baiomys taylori Thomas) was 0.07 ha.…”
Section: Experimental Designmentioning
confidence: 99%
“…It can be divided into population models, ecosystem models and landscape models [47] GIS/RS Combine with GIS technology, other ecological models, and the improved algorithm, to carry out EcoRA in the spatial and temporal scales [17,72] Computer software…”
Section: Methodsmentioning
confidence: 99%